IDNLearn.com provides a collaborative environment for finding and sharing answers. Ask anything and receive well-informed answers from our community of experienced professionals.
Sagot :
To find the first term of the arithmetic progression (AP), let's denote the first term by [tex]\(a\)[/tex] and the common difference by [tex]\(d\)[/tex].
Given:
1. The [tex]\( (4p)^{\text{th}} \)[/tex] term of the AP is 15 more than the [tex]\( (3p)^{\text{th}} \)[/tex] term.
2. The [tex]\( (p+1)^{\text{th}} \)[/tex] term is 18.
For an AP, the [tex]\( n^{\text{th}} \)[/tex] term is given by:
[tex]\[ a_n = a + (n-1)d \][/tex]
Using this formula, write the expressions for the given terms:
### Step 1: Express the [tex]\( (4p)^{\text{th}} \)[/tex] and [tex]\( (3p)^{\text{th}} \)[/tex] terms
- The [tex]\( (4p)^{\text{th}} \)[/tex] term:
[tex]\[ a + (4p-1)d \][/tex]
- The [tex]\( (3p)^{\text{th}} \)[/tex] term:
[tex]\[ a + (3p-1)d \][/tex]
According to the given condition:
[tex]\[ a + (4p-1)d = 15 + \left(a + (3p-1)d\right) \][/tex]
### Step 2: Simplify the above equation
[tex]\[ a + 4pd - d = 15 + a + 3pd - d \][/tex]
Cancel common terms from both sides:
[tex]\[ 4pd - d = 15 + 3pd - d \][/tex]
Simplify by eliminating [tex]\( -d \)[/tex]:
[tex]\[ 4pd = 15 + 3pd \][/tex]
Isolate the term involving [tex]\(pd\)[/tex]:
[tex]\[ 4pd - 3pd = 15 \][/tex]
[tex]\[ pd = 15 \][/tex]
### Step 3: Use the expression for the [tex]\( (p+1)^{\text{th}} \)[/tex] term
The [tex]\( (p+1)^{\text{th}} \)[/tex] term:
[tex]\[ a + (p+1-1)d = a + pd \][/tex]
We are given:
[tex]\[ a + pd = 18 \][/tex]
### Step 4: Substitute [tex]\( pd = 15 \)[/tex] into the above equation
[tex]\[ a + 15 = 18 \][/tex]
[tex]\[ a = 18 - 15 \][/tex]
[tex]\[ a = 3 \][/tex]
Therefore, the first term [tex]\(a\)[/tex] is [tex]\( \boxed{3} \)[/tex].
So, the correct answer is [tex]\( \text{A. } 3 \)[/tex].
Given:
1. The [tex]\( (4p)^{\text{th}} \)[/tex] term of the AP is 15 more than the [tex]\( (3p)^{\text{th}} \)[/tex] term.
2. The [tex]\( (p+1)^{\text{th}} \)[/tex] term is 18.
For an AP, the [tex]\( n^{\text{th}} \)[/tex] term is given by:
[tex]\[ a_n = a + (n-1)d \][/tex]
Using this formula, write the expressions for the given terms:
### Step 1: Express the [tex]\( (4p)^{\text{th}} \)[/tex] and [tex]\( (3p)^{\text{th}} \)[/tex] terms
- The [tex]\( (4p)^{\text{th}} \)[/tex] term:
[tex]\[ a + (4p-1)d \][/tex]
- The [tex]\( (3p)^{\text{th}} \)[/tex] term:
[tex]\[ a + (3p-1)d \][/tex]
According to the given condition:
[tex]\[ a + (4p-1)d = 15 + \left(a + (3p-1)d\right) \][/tex]
### Step 2: Simplify the above equation
[tex]\[ a + 4pd - d = 15 + a + 3pd - d \][/tex]
Cancel common terms from both sides:
[tex]\[ 4pd - d = 15 + 3pd - d \][/tex]
Simplify by eliminating [tex]\( -d \)[/tex]:
[tex]\[ 4pd = 15 + 3pd \][/tex]
Isolate the term involving [tex]\(pd\)[/tex]:
[tex]\[ 4pd - 3pd = 15 \][/tex]
[tex]\[ pd = 15 \][/tex]
### Step 3: Use the expression for the [tex]\( (p+1)^{\text{th}} \)[/tex] term
The [tex]\( (p+1)^{\text{th}} \)[/tex] term:
[tex]\[ a + (p+1-1)d = a + pd \][/tex]
We are given:
[tex]\[ a + pd = 18 \][/tex]
### Step 4: Substitute [tex]\( pd = 15 \)[/tex] into the above equation
[tex]\[ a + 15 = 18 \][/tex]
[tex]\[ a = 18 - 15 \][/tex]
[tex]\[ a = 3 \][/tex]
Therefore, the first term [tex]\(a\)[/tex] is [tex]\( \boxed{3} \)[/tex].
So, the correct answer is [tex]\( \text{A. } 3 \)[/tex].
Your participation means a lot to us. Keep sharing information and solutions. This community grows thanks to the amazing contributions from members like you. Find reliable answers at IDNLearn.com. Thanks for stopping by, and come back for more trustworthy solutions.